Development of Creative Alternative Assessments for Mathematics Learning Using a Design Thinking Approach - Purwosetiyono, F.X. Didik; Shodiqin, Ali; Wardani, Theodora Indriati (Universitas Islam Sultan Agung, 2024)
Abstract. Alternative assessments in mathematics education face several challenges that need to be designed to measure students' abilities holistically. The objectives of this research are: 1) to determine the feasibility of developing creative alternative mathematics assessments using a design thinking approach, and 2) to assess the effectiveness of mathematics learning using alternative assessments with a design thinking approach. The research sample consists of graduate students from the Mathematics Education program at PGRI University Semarang. This study employs the development model proposed by Plomp J and Nieveen N. The development of creative alternative mathematics assessments using a design thinking approach is analyzed through: a) pretest data, b) posttest data, and c) effectiveness analysis, including n-gain calculations (pretest-posttest) and completeness testing. The findings indicate that: 1) the development of creative alternative mathematics assessments with a design thinking approach is deemed feasible for use, and 2) the effectiveness of alternative mathematics assessments using a design thinking approach is evidenced by: a) an increase in the average learning outcomes of students before and after using the creative alternative mathematics assessment with a design thinking approach, and b) student learning outcomes meeting the completeness criteria when using the creative alternative mathematics assessment with a design thinking approach. Keywords: Development; Alternative Assessment; Mathematics Learning; Design Thinking